LEGAL PROTECTION OF NON WAGE WORKERS’ RIGHTS AFTER OMNIBUS LAW - Danendra, Ravi; Handayani, I Gusti Ayu Ketut Rachmi; Jaelani, Abdul Kadir; Najicha, Fatma Ulfatun (Jurisprudentie : Jurusan Ilmu Hukum Fakultas Syariah dan Hukum, 2021)
This study aims to analyze the legal protection of non-wage workers’ rights after enacting the omnibus law. The type of research used is normative legal research. Normative legal analysis prioritizes library research by collecting data from libraries and other places. The research data used is secondary data. Secondary data collection tools in the form of books related to the theory and concept of the object of research, related articles, scientific writing literature, and so on through library research. The study results show that the legal protection of the rights of non-wage workers after omnibus Law is very minimal and does not reflect the provisions of Article 28 D paragraph (2) of the 1945 Constitution. Keyword: Protection; Wage; Employment.